Michel Foucault e a dominação: contribuições para a sociologia - Freire, Alyson Thiago Fernandes (2014)
In this master s thesis I intend to carry out an interpretation of Michel Foucault s thought that points out the relations and theoretical, conceptual and thematic consequences with sociology in his work and theoretical propositions. For my argumentation and analysis I take as a base a specific part of his thought: the problem of domination in modern societies in the genealogic texts in the decade of 1970. It s about to identify how Foucault does his analysis of the relations of domination and the use of the power with the objective to suggest and point out his contribution to sociological analysis of domination. I will discuss the foucaultian program of the study of domination from four units of analysis: person constitution, knowledge, power and truth. The structure and division of the chapters will follow the specific and detailed study of each of those units of analysis, prioritizing their theoretical sense and consequences to the sociology. Thus, in the first chapter, I will highlight a little more the relations of affinity and the convergences between Foucault and the sociology in a way to offer more elements to justify the general objectives that this work intends to achieve. In the second chapter, I will analyze the subject of domination in Foucault s thought, discussing his basic presuppositions and its intrinsic relation with the heart of the foucaultian philosophical project, the person constitution. In turn, in the third and fourth chapter, I will discuss the interdependence between knowledge and power as an essential and opaque dimension of the ways of modern domination. In the fifth chapter, I will analyze the relation between domination and the truth discourse production